Data and knowledge needs for improving science and policy for peatlands in Canada in a changing world: insights from Global Peatlands Initiative Workshop, June 2023 - Kara L. Webster; Maria Strack; Nicole Balliston; Marissa A. Davies; E. Kathryn Hettinga; Miranda Hunter; Kimberly Kleinke; Megan Schmidt; Carlos Barreto; Melanie Bird; Kristen Blann; Kelly Bona; et al. (FACETS)
Knowledge and data on the current function, future threats, and benefits of peatlands in Canada are required to support evidence-based decision-making to ensure they continue to provide critical ecosystem services. This is particularly relevant for Canada, given the large expanse of relatively intact peatland area. There is a need, not only to standardize protocols, but also to prioritize types of information and knowledge that can best meet conservation and management goals. This was the challenge posed to the participants of the Global Peatlands Initiative workshop in June 2023 in Quebec City, Quebec, Canada. Participants were composed of researchers using primarily Western science approaches that use peatland data for carbon accounting, policy or sustainable land use, reclamation/restoration, conservation, wildlife, and water resources applications. For seven peatland data categories (hydrometeorological and environmental sensing; peat coring and depth; greenhouse gas monitoring; biodiversity; vegetation, woody debris, and litter; Traditional Knowledge; water quality), three priority measurements were identified and recommendations for their collection were discussed. The key recommendations from the workshop were to (1) create standardized, yet flexible protocols; (2) coordinate field data collection where possible; (3) weave more Traditional Knowledge into understanding of peatlands; (4) create an atlas of existing peatland information; (5) scope opportunities to create a network of peatland “super sites”.